Effect of Various Concentration of Vegetable Protein in Hair Mask on The Hair Texture - Helen, Ivony; Hadinoto, Idajani; Hadisoewignyo, Lannie; Soegianto, Lisa (Indonesian Journal of Cancer Chemoprevention, 2011)
Effect of various concentrations of vegetable protein in hair mask on the hair texture including hair smoothness, hair shining, hair strength, and morphology of hair had been studied. Concentrations of vegetable protein are made 5%, 7.5%, and 10%. The hair mask was evaluated such as organoleptic, pH, viscosity, and allergy test. Hair mask used in six subjects that have damage hair for 8 times every 2 days. Then, the hair mask was evaluated such as hair smooth and hair shine that used tree trained panel and analyzed using non parametric method Q Cochran. Hair strength was evaluated using autographÃÂ  thenÃÂ  theÃÂ  resultsÃÂ  wereÃÂ ÃÂ ÃÂ  analyzesÃÂ  usingÃÂ  ANOVAÃÂ  testÃÂ  (p<0.05),ÃÂ  whileÃÂ  hair morphologyÃÂ  wasÃÂ  evaluatedÃÂ  usingÃÂ  scanningÃÂ  microscopeÃÂ  electronÃÂ  (SEM).ÃÂ  The experimentalÃÂ  resultsÃÂ  showedÃÂ  thatÃÂ  vegetableÃÂ  proteinÃÂ  inÃÂ  hairÃÂ  maskÃÂ  increasedÃÂ  hair smoothness, hair strength, and morphology of damaged hair but did not give effect for hair shining. Various concentrations of vegetable protein (5%, 7.5%, and 10%) on hair mask given the same effect in hair texture (hair smoothness, hair strength, and hair morphology).